2021
DOI: 10.1161/jaha.120.020080
|View full text |Cite
|
Sign up to set email alerts
|

Extent of Coronary Artery Disease in Patients With Stenotic Bicuspid Versus Tricuspid Aortic Valves

Abstract: Background Bicuspid aortic valve (BAV) is the most common congenital cardiac malformation, which is often complicated by aortic valve stenosis (AoS). In tricuspid aortic valve (TAV), AoS strongly associates with coronary artery disease (CAD) with common pathophysiological factors. Yet, it remains unclear whether AoS in patients with BAV is also associated with CAD. This study investigated the association between the aortic valve morphological features and the extent of CAD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 36 publications
3
30
0
Order By: Relevance
“…Comparison of echocardiographic characteristics were already made in a previous study, which showed higher aortic valve gradients in BAV patients (peak gradient of 73 vs 62 mm Hg, p<0.001). 3 Subanalysis showed a higher prevalence of risk factors hypercholesterolaemia and diabetes mellitus in TAV-AoS vs TAV-AR (both p<0.001), as well as with a higher prevalence of previous CAD (corrected OR (age and sex) for TAV-AR vs TAV-AoS: 1.08 (95% CI 1.06 to 1.10); p=0.001). Comparison of BAV-AoS patients with BAV-AR patients only showed a higher prevalence of diabetes mellitus in BAV-AoS patients (p<0.001).…”
Section: Cardiovascular Burden: Bav Versus Tav Patientsmentioning
confidence: 93%
See 4 more Smart Citations
“…Comparison of echocardiographic characteristics were already made in a previous study, which showed higher aortic valve gradients in BAV patients (peak gradient of 73 vs 62 mm Hg, p<0.001). 3 Subanalysis showed a higher prevalence of risk factors hypercholesterolaemia and diabetes mellitus in TAV-AoS vs TAV-AR (both p<0.001), as well as with a higher prevalence of previous CAD (corrected OR (age and sex) for TAV-AR vs TAV-AoS: 1.08 (95% CI 1.06 to 1.10); p=0.001). Comparison of BAV-AoS patients with BAV-AR patients only showed a higher prevalence of diabetes mellitus in BAV-AoS patients (p<0.001).…”
Section: Cardiovascular Burden: Bav Versus Tav Patientsmentioning
confidence: 93%
“…All included hospital patients were surgically treated between 2006 and 2019 and were obtained from a retrospective study conducted at the Leiden University Medical Center (LUMC) in the Netherlands. 3 Patient consent was waived. Subsequently, the atherosclerotic disease burden of each group was compared with that of the corresponding (matched) age cohort for the general population.…”
Section: Study Populationmentioning
confidence: 99%
See 3 more Smart Citations